Biorefinery development for the production of polyphenols, algal biomass and lipids using olive processing industry waste - Nicodemou, Andonia; Kallis, Michalis; Koutinas, Michalis (My University, 2023)
A biorefinery was developed employing olive pomace and table olive processing wastewater for the manufacture of polyphenols, lipids and algal biomass. Following extraction of pomace oil, olive pomace was subjected to dilute acid hydrolysis and enzyme hydrolysis under different conditions aiming to maximise the content of polyphenols and sugars formed in the hydrolysate produced for application in subsequent resin adsorption/desorption and microalgal fermentation processes. Hydrolysis of 100 kg exhausted olive pomace performed under the most efficient conditions yielded release of 54.5 kg of sugars and 3.2 kg of polyphenols. Polyphenols were recovered from olive pomace hydrolysates and table olive processing wastewater via adsorption/desorption employing different polymeric resins. Application of XAD16N and PAD900 resins exhibited the highest overall polyphenols recovery, that reached 79.5% and 58.0% for table olive processing wastewater and exhausted olive pomace extracts respectively. The hydrolysates generated following polyphenols recovery were evaluated as feedstocks for lipids production by Scenedesmus obliquus and Isochrysis galbana, demonstrating maximum biomass and lipid productivity that reached 190 mg L−1 d−1 and 61.4 mg L−1 d−1 for S. obliquus, as well as 32 mg L−1 d−1 and 8.4 mg L−1 d−1 for I. galbana respectively. I. galbana accumulated high docosahexaenoic acid content that ranged between 8.4 and 9.5 mg g−1 of ash-free dry weight in fermentations of the hydrolysates developed confirming that the strain could serve as an advanced bioproducer of polyunsaturated fatty acids in microalgal biorefineries.
Keywords: Biorefinery; Olive pomace; Table olive processing wastewater; Polyphenols; Microalgae; Polyunsaturated fatty acids